Managing Innovation and Collaboration towards Sustainable Post-Mining Land Reclamation: Systematic Literature Review - Muhardi Muhardi; Cici Cintyawati (Journal of Governance, 2022)
Abstract: Post-mining land reclamation is getting more attention from many parties since it is perceived as a solution for creating more sustainable mining lands in Indonesia. Reclaiming mining land can reduce negative impacts and create more productive lands to generate more economic benefits. Collaboration and innovation from various parties such as the government, communities, private companies, and other stakeholders are needed to achieve this goal. This study explores data and information related to post-mining land reclamation alternatives by applying the concept of collaboration (co-creation) and innovation among stakeholders. The method used in this research is Systematic Literature Review. This method aims to review the relevant literature through a systematic process. There are 11 articles used as a source of literature review, which is grouped based on concepts and discussions following the topics raised in this study. The results of this study are a post-mining land reclamation idea and the concept of collaboration between the stakeholders to realize a sustainable post-mining land reclamation in Indonesia.Keywords: post-mining land; collaboration; innovation; sustainability